2007
DOI: 10.1029/2006ja012197
|View full text |Cite
|
Sign up to set email alerts
|

Signature of the 29 March 2006 eclipse on the ionosphere over an equatorial station

Abstract: [1] This study documents some results of the effect of the 29 March 2006 eclipse on the ionosphere over Ilorin, Nigeria (longitude 4.57°E, latitude 8.53°N, dip 4.1°S), an equatorial station in the West African region. The maximum obscuration of the eclipse at this station was 99 percent and it occurred before midday. True height electron density profile analysis below the F2 peak was employed in the study. The effect on the E and F1 layers was a drastic decrease in electron density, with maximum decrease perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
55
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 15 publications
9
55
3
Order By: Relevance
“…The results of Skinner (1967) were for a period of high solar activity when the F1 region is not very distinct from the F2, and 68 % reduction was noticed in the electron density of the F1 region. Adeniyi et al (2007) have also shown that maximum decrease in the peak electron density as deduced from the critical frequency for F1 was 68 % for the total solar eclipse of 29 March 2006 during low solar activity period. In Fig.…”
Section: F1 Layermentioning
confidence: 89%
See 1 more Smart Citation
“…The results of Skinner (1967) were for a period of high solar activity when the F1 region is not very distinct from the F2, and 68 % reduction was noticed in the electron density of the F1 region. Adeniyi et al (2007) have also shown that maximum decrease in the peak electron density as deduced from the critical frequency for F1 was 68 % for the total solar eclipse of 29 March 2006 during low solar activity period. In Fig.…”
Section: F1 Layermentioning
confidence: 89%
“…The eclipse effect in the F2 region is larger at high solar activity than at low solar activity. In a recent study, the signatures of a total solar eclipse on ionospheric E, F1 and F2 regions, during the forenoon hours, have been reported by Adeniyi et al (2007), as observed over equatorial station Ilorin, Nigeria. In the present investigation, we find that the decrease in electron density occurs throughout the E and F1 layer heights at about the same time, while, in the F2 region, the electron density decrease began at lower heights and extended progressively towards the layer peak.…”
Section: Introductionmentioning
confidence: 99%
“…The Ilorin site has an advantage of being a Baseline Surface Radiation Network (BSRN) candidate site with several operational instruments for environmental monitoring (Pinker et [3]. These include Pyranometers, Pirgeometers, Pressure and temperature sensors and AERONET Cimel sensors.…”
Section: Methodsmentioning
confidence: 99%
“…Temperature: The temperature was measured on a flat rooftop at a site synonymous with Adeniyi, et al (2006). It showed a drop in value between 09:08 and 09:58 GMT with a minimum at about 9.32 GMT (Figure 1).…”
Section: Direct Solar Radiationmentioning
confidence: 99%
See 1 more Smart Citation